Design and Implementation of PV based Energy Harvester for WSN Node with MAIC algorithm - RAJENDRAN, H.; RAMABADRAN, R.; SANKARARAJAN, R. (Advances in Electrical and Computer Engineering, 2015)
Wireless sensor networks (WSNs) are hardly in need of an additional source of power other than the normally used batteries, to increase the lifetime considerably. In this paper, mathematical modeling of photovoltaic energy harvesting (PVEH) system for the WSN is presented. The system comprises of the solar PV panel, boost converter as maximum power point tracker with moving averaged incremental conductance (MAIC) maximum power point (MPP) algorithm, Ni-MH battery for energy storage, compensator, buck regulator and the mathematically modeled WSN mote. MAIC algorithm is proposed to avoid the effect of drastic variations in input irradiance, in locking the MPP point. WSN mote is modeled in both active and sleep state based on the power consumption. To maintain the voltage stability, proper compensator has been designed for the proposed system. The performance of the system is tested for dynamic variations of environmental conditions using MATLAB simulation. The proposed system has 50 to 60 percent improved conversion efficiency when compared to the conventional direct coupling method. The parameters of the photovoltaic panel model have been validated through experimentation. Also the practical verification of the operation of MPPT circuit has been performed.